Pilgrimage of Love : Moltmann on the Trinity and Christian Life. - McDougall, Joy Ann (AAR Reflection and Theory in the Study of Religion Ser., 2005)
Offers a reading of Moltmann's major theological writings over the years, from his first major book, "The Theology of Hope". This book traces the development of Moltmann's doctrine of the Trinity and its implications for ethics.